2021
DOI: 10.1111/famp.12742
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal anxiety in couples during a global pandemic: Considering loss, attachment behaviors, and trauma coping self‐efficacy

Abstract: The COVID-19 (SARS-COV-2) pandemic has had a significant impact on multiple domains of daily functioning in communities, families, and couples. Research on couple dynamics amid mass stress events using dyadic data is still limited. As such, the current study employed a cross-lagged panel design with 535 cisgender, heterosexual couples to explore longitudinal paths between pandemic-related loss, attachment behaviors, trauma coping self-efficacy, and anxiety symptoms. Data were collected at three time points bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The literature on couples examining loss in the wake of the pandemic is still developing. However, findings from the current study are in line with other recent work showing partner effects of resource loss; interestingly and perhaps hopefully it also suggests the potentially mobilizing effect of loss on a relationship in that higher resource loss in one partner associated with higher levels of attachment behaviors in the other partner (Banford Witting et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The literature on couples examining loss in the wake of the pandemic is still developing. However, findings from the current study are in line with other recent work showing partner effects of resource loss; interestingly and perhaps hopefully it also suggests the potentially mobilizing effect of loss on a relationship in that higher resource loss in one partner associated with higher levels of attachment behaviors in the other partner (Banford Witting et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Yet, to date, the effects of the pandemic for couple and family systems appear mixed, with both positive (increased closeness) and negative (increased conflict) outcomes noted (Günther-Bel et al, 2020). To further illustrate the mix of potentially positive and detrimental pandemic-related outcomes for couple relationships, recent research has demonstrated that greater anxiety symptoms during the pandemic associated with greater resource loss within partners 3 months later in a dyadic study of couples in the early months of pandemic-related shutdowns, suggesting that depletion or vulnerability may cascade into further losses, as would be line with assumptions of COR theory (Banford Witting et al, 2021; Hobfoll et al, 2016). On the other hand, pandemic-related resource loss reported by one partner associated with higher levels of couple attachment behaviors 3 months later in the other partner (Banford Witting et al, 2021), potentially suggesting that couple systems may activate to compensate for pandemic-related disruption.…”
Section: Resource Loss and The Pandemic: Theoretical Lensmentioning
confidence: 87%
See 1 more Smart Citation
“…Although it is important to understand the inter‐resonance of couple processes with respect to mental health outcomes, current scholarly work incorporating data from more than one partner to examine consequences of large‐scale stressors (i.e., disasters) is infrequent (see Banford Witting et al., 2020 for a review). As such, the current study was designed to contribute to burgeoning relationship‐oriented research surrounding the pandemic's impact (see Banford Witting et al., 2021). Specifically, the study aims include an examination of anxiety in couples over three waves across time during the 6 months early in the series of US pandemic‐related shutdowns as a function of sense of community and world assumptions.…”
Section: Introductionmentioning
confidence: 99%